Factors that influence non‐word repetition performance in children with and without persistent speech sound disorders. Issue 6 (20th August 2021) - Farquharson, Kelly; Hogan, Tiffany P.; Fox, Annie B.
Abstract: Background: Nonword repetition (NWR) is a common phonological processing task that is reported to tap into many cognitive, perceptual, and motor processes. For this reason, NWR is often used in assessment batteries to aid in verifying the presence of a reading or language disorder. Aims: To examine the extent to which child‐ and item‐level factors predict the probability of a correct response on a non‐word repetition (NWR) task in a sample of children with persistent speech sound disorders (P‐SSDs) compared with their typically developing peers. Methods & Procedures: A total of 40 American‐English‐speaking children were tested on an NWR task for which the stimuli were manipulated for phonological neighbourhood density and list length. Additional measures of vocabulary and word reading were also administered. Outcomes & Results: Children who were typically developing were 1.82 times more likely than children with P‐SSD to respond correctly. The item‐level factor of phonological neighbourhood density influenced performance, but only for the P‐SSD group, and only at certain list lengths. Vocabulary and word‐reading ability also influenced NWR task performance. Conclusions & Implications: Children with P‐SSD present as a complex and heterogeneous group. Multiple factors contribute to their ability to perform phonological tasks such as NWR. As such, attention to the item‐level factors in screenings and assessments is necessary to ensure that appropriate decisions are made regarding diagnosis and subsequent treatment. What this paper adds: What is already known on the subject?: Good expressive vocabulary is important for children with speech sound disorders; it can aid in their performance on phonological processing tasks like NWR. Nonword repetition may be a helpful test/ subtest to add to assessment batteries when evaluating children with speech sound disorders. What this paper adds to existing knowledge?: Vocabulary and word reading abilities must also be measured for children with SSDs, to observe the bigger picture of their linguistic abilities. What are the potential or actual clinical implications of this work?: The relation between word reading and speech sound production influences performance on phonological processing tasks.